2018
DOI: 10.1016/j.cels.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Functional Analysis Distinguishes Pathogenic, Nonpathogenic, and Compensatory Transcriptional Changes in Neurodegeneration

Abstract: Discriminating transcriptional changes that drive disease pathogenesis from nonpathogenic and compensatory responses is a daunting challenge. This is particularly true for neurodegenerative diseases, which affect the expression of thousands of genes in different brain regions at different disease stages. Here we integrate functional testing and network approaches to analyze previously reported transcriptional alterations in the brains of Huntington disease (HD) patients. We selected 312 genes whose expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 72 publications
(94 reference statements)
3
37
0
Order By: Relevance
“…Verifying this effect in multiple model organisms increases confidence in this observation and suggests that SERPINA1 could potentially prove useful as a target for treating HD. Interestingly, SERPINA1 expression is low in the healthy brain but it is upregulated in several disease conditions, consistent with a potential role in neuroinflammation (Abu-Rumeileh et al, 2020;Cabezas-Llobet et al, 2018;Gollin et al, 1992;Peng et al, 2015), and we previously showed that other genes in the subnetwork implicated in neuroinflammation can be manipulated to lower mHTT protein levels (Al-Ramahi et al, 2018). SERPINA1 may thus warrant investigation as a target for other neurological disorders as well.…”
Section: Reducing Serpina1 Function Mitigates Behavioral Impairments supporting
confidence: 76%
“…Verifying this effect in multiple model organisms increases confidence in this observation and suggests that SERPINA1 could potentially prove useful as a target for treating HD. Interestingly, SERPINA1 expression is low in the healthy brain but it is upregulated in several disease conditions, consistent with a potential role in neuroinflammation (Abu-Rumeileh et al, 2020;Cabezas-Llobet et al, 2018;Gollin et al, 1992;Peng et al, 2015), and we previously showed that other genes in the subnetwork implicated in neuroinflammation can be manipulated to lower mHTT protein levels (Al-Ramahi et al, 2018). SERPINA1 may thus warrant investigation as a target for other neurological disorders as well.…”
Section: Reducing Serpina1 Function Mitigates Behavioral Impairments supporting
confidence: 76%
“…of Atxn1 154Q/2Q mice, a region of the mouse CNS that lacks the anatomical portion affected by SCA1, likely fall into the nonconsequential category described by Al-Ramahi et al (37).…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, differentially expressed genes may define non-causal perturbations—such changes may represent candidates as biomarkers for the neuronal injury accompanying neurofibrillary tangle pathology. Similar to recently published work [ 54 ], in order to identify potential causal gene expression changes, we integrated our findings with available results from 3 published, unbiased Drosophila screens, together defining 84 genetic modifiers of Tau-mediated neurotoxicity [ 23 – 25 ]. Among these, 37 genes were differentially expressed in the transcriptome and/or proteome (either Tau WT or Tau R406W ) (Table 4 and Additional file 2 : Table S10).…”
Section: Resultsmentioning
confidence: 99%